Giant concha bullosa. (15th January 2014) - Derin, Serhan; Deveer, Mehmet; Sahan, Murat; Beydilli, Halil
Abstract : Concha bullosa is the most frequently encountered anatomical variation of the lateral nasal wall characterised with pneumatisation of the middle concha. The incidence of middle concha bullosa varies between 14% and 53%. Patients may often complain of nasal congestion and may in some cases suffer episodes of recurrent acute rhinosinusitis. In this article we present a case of nasal obstruction with an unusually large concha bullosa.